Redefining Local Government Authority in Natural Resource Management Following Centralization - Irmanjaya Thaher; Dzaki M. Ihsan; Margaretha Hanita (Hakamain: Journal of Sharia and Law Studies, 2024)
This study examines the redefinition of local government authority in natural resource management following the recent trend toward centralization in Indonesia. Although decentralization was originally designed to strengthen regional autonomy and improve public participation in managing natural resources, subsequent regulatory reforms have shifted significant authority to the central government, creating new legal and institutional challenges. This research aims to analyze the implications of this centralization for the distribution of governmental powers, environmental governance, and sustainable resource management. The study employs a normative juridical method using statutory, conceptual, and comparative approaches. Primary legal materials include the 1945 Constitution of the Republic of Indonesia, Law Number 23 of 2014 on Regional Government and its amendments, Law Number 3 of 2020 on Mineral and Coal Mining, Law Number 11 of 2020 as amended by Law Number 6 of 2023 on Job Creation, Constitutional Court decisions, and relevant scholarly literature. The findings indicate that the centralization of natural resource governance has reduced the decision-making capacity of local governments, weakened community participation, and generated overlapping institutional responsibilities despite improving regulatory uniformity and investment certainty. The study concludes that a balanced redistribution of authority is necessary to strengthen cooperative governance, enhance environmental accountability, and ensure that local governments retain meaningful roles in managing regional natural resources. This study contributes to constitutional and administrative law by proposing a collaborative governance framework that reconciles national policy objectives with regional autonomy to achieve sustainable and equitable natural resource management.